Synthesis of Metal-Organic Framework (MOF) Cr-PTC-HIna for Heavy Metal Ion Adsorption - Nurhasni, Nurhasni; Adawiah, Adawiah; Wahyudin, Wahyudin; Hadriyani, Rizka; Andriyani, Leni; Fadhilla, Rizkha; Zulys, Agustino; Sukandar, Dede (Bulletin of Chemical Reaction Engineering & Catalysis, 2024)
As an adsorbent material, Metal-Organic Framework (MOF) provides several advantages, such as large surface area and pore volume, as well as stability in aqueous systems both in acidic, basic, and neutral conditions. The research successfully made a metal organic framework (MOF) from chromium and perylene that was modulated by isonicotinic acid. This was done using three different methods: hydrothermal (Cr-PTC-HIna-HT), solvothermal (Cr-PTC-HIna-ST), and sonochemical (Cr-PTC-HIna-SC). The Cr-PTC-HIna-SC showed the greatest Pb2+ ion adsorption capacity. The optimum adsorption of Pb2+ ions occurred at 150 ppm Pb2+ ion concentration, pH 5, 90 minutes of contact time, and an adsorption capacity of 149.95 mg/g at 35 °C. The dominant adsorption isotherm model is the Langmuir isotherm model with R2 = 0.9867 and follows the pseudo-second-order. The selectivity test showed that Cr-PTC-HIna-SC MOF could adsorb more Cd2+ ions than Pb2+ ions, with 250 mg/g being the best amount.